2010
DOI: 10.1111/j.1538-7836.2010.03806.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide‐sensitive guanylyl cyclase is the only nitric oxide receptor mediating platelet inhibition

Abstract: Summary. Background: The nitric oxide (NO)/cyclic guanosine monophosphate (cGMP) signaling cascade is involved in the precise regulation of platelet responses. NO released from the endothelium is known to activate NO-sensitive guanylyl cyclase (NO-GC) in platelets. By the generation of cGMP and subsequent activation of cGMP-dependent protein kinase (PKG), NO-GC mediates the reduction of the intracellular calcium and inhibits platelet adhesion and aggregation. However, NO has been postulated to influence these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
89
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(97 citation statements)
references
References 36 publications
2
89
2
1
Order By: Relevance
“…It has been recently demonstrated that physiologically relevant concentrations of DEA/NONOate and other NO donors act in platelets exclusively through activation of soluble guanylyl cyclase, driving the production of cGMP (13). cGMP is an important signaling molecule with its own downstream effectors but may also act in part by influencing cAMP signaling.…”
Section: P2y 12 Receptor Blockade Greatly Increases the Inhibition Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been recently demonstrated that physiologically relevant concentrations of DEA/NONOate and other NO donors act in platelets exclusively through activation of soluble guanylyl cyclase, driving the production of cGMP (13). cGMP is an important signaling molecule with its own downstream effectors but may also act in part by influencing cAMP signaling.…”
Section: P2y 12 Receptor Blockade Greatly Increases the Inhibition Ofmentioning
confidence: 99%
“…NO acts by directly activating platelet guanylyl cyclase, causing an increase in intraplatelet cGMP (13). Although this cGMP pathway is distinct from the cAMP pathway that is modulated by PGI 2 and P2Y 12 , earlier studies have shown that activation of these two inhibitory pathways produces a synergistic antiplatelet effect (18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Substantial evidence supports a critical role for PKG in mediating the anti-platelet aggregation action caused by cGMP elevating agents such as endothelium-derived NO (EDNO) and exogenous nitrovasodilators (Walter & Gambaryan, 2009;Dangel et al, 2010). PKG I is the predominate isoform of the enzyme in platelets.…”
Section: Anti-platelet Aggregation Actionmentioning
confidence: 99%
“…In the NO/ sGC/cGMP pathway, endogenous NO synthesized by NO synthases (NOSs) activates soluble guanylate cyclase (sGC) in cells such as muscles, neurons and leukocytes. Active sGC catalyzes the synthesis of cyclic GMP (cGMP) (7). Then cGMP activates three effector molecules: the cGMP-dependent protein kinase G (PKG), cGMP-regulated phosphodiesterases, and cGMP-gated ion channels (8).…”
Section: Introductionmentioning
confidence: 99%